2011
DOI: 10.1021/la200003n
|View full text |Cite
|
Sign up to set email alerts
|

Study of PEGylated Lipid Layers as a Model for PEGylated Liposome Surfaces: Molecular Dynamics Simulation and Langmuir Monolayer Studies

Abstract: We have combined Langmuir monolayer film experiments and all-atom molecular dynamics (MD) simulation of a bilayer to study the surface structure of a PEGylated liposome and its interaction with the ionic environment present under physiological conditions. Lipids that form both gel and liquid-crystalline membranes have been used in our study. By varying the salt concentration in the Langmuir film experiment and including salt at the physiological level in the simulation, we have studied the effect of salt ions … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
120
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 102 publications
(132 citation statements)
references
References 104 publications
12
120
0
Order By: Relevance
“…However, recent molecular dynamics simulations and Langmuir monolayer measurements suggested that PEG-lipids may insert their polyether moiety into the fluid phase phospholipid bilayers. 25) In this regard, the quantitative assessment of liposome membrane fluidity by using the GP values for Prodan (Fig. 6A) indicates that the hydrophilic region in liposome membrane appears to be somewhat perturbed by incorporated PEG-lipids.…”
Section: Discussionmentioning
confidence: 95%
“…However, recent molecular dynamics simulations and Langmuir monolayer measurements suggested that PEG-lipids may insert their polyether moiety into the fluid phase phospholipid bilayers. 25) In this regard, the quantitative assessment of liposome membrane fluidity by using the GP values for Prodan (Fig. 6A) indicates that the hydrophilic region in liposome membrane appears to be somewhat perturbed by incorporated PEG-lipids.…”
Section: Discussionmentioning
confidence: 95%
“…A common route to designing sterically stable liposomes is via the grafting of polyethylene glycol (PEG) chains to the lipid head groups [6][7][8]. PEG chains have been shown to control the size [8][9][10], morphology [10][11][12], compressibility [9,13], encapsulation efficiency [8,14,15] and permeability of liposomes [8,14]. Experimental and computational studies have investigated the morphology of binary mixtures of PEGylated and non-PEGylated lipids [10,11,13,16]; and their dynamics and stability [6,11,13], for species composed of the same hydrocarbon tail groups [8,10,14,17,18].…”
Section: Introductionmentioning
confidence: 99%
“…9,14 For our study we chose an intermediate chain length, namely PEG2000, since it is commonly used for nanoparticle functionalization and in PEGylated liposomes. 18,25,53 The small SFG signal present in the amide I region for the mixed monolayer with 5 mol% DMPE-PEG2000, is a feature sometimes observed, even in absence of proteins, and is most likely caused by a contribution from the water bending mode. However, below we will consider differential spectra with and without protein, so that this is not a problem (for further details see Section SIIB and Fig.…”
mentioning
confidence: 99%